2020
DOI: 10.1108/lht-02-2020-0034
|View full text |Cite
|
Sign up to set email alerts
|

Students' intention to adopt e-government learning services: a developing country perspective

Abstract: PurposeIn any developing country, the critical benefits for ensuring proper utilization of e-government learning services have basically emerged from the integration of underlying processes – not only across different levels of government but also across different functions and agencies. The literature showed a notable lack of research to underline the limited use of e-government learning services in a university setting. Therefore, this study was conducted to examine students' intention to adopt e-government … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 106 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…Other scholars supported that information usefulness boosts information adoption toward social media (Park, 2020) and health information skills under COVID-19 (Shehata, 2020). Al-Omairi et al (2020) found that relevant, timely information acts a crucial role in fostering credibility toward e-government services. Likewise, relevant MERS-specific information via social media contributes to perceived threat (Yoo et al, 2016).…”
Section: Conceptual Model and Hypotheses 231 Information Relevance (Rel)mentioning
confidence: 99%
See 1 more Smart Citation
“…Other scholars supported that information usefulness boosts information adoption toward social media (Park, 2020) and health information skills under COVID-19 (Shehata, 2020). Al-Omairi et al (2020) found that relevant, timely information acts a crucial role in fostering credibility toward e-government services. Likewise, relevant MERS-specific information via social media contributes to perceived threat (Yoo et al, 2016).…”
Section: Conceptual Model and Hypotheses 231 Information Relevance (Rel)mentioning
confidence: 99%
“…Older people generate source credibility if they feel confident about formers and content providers know accurate, truthful information. Creators build their credibility due to the reputation and integrity to assure that the users receive precise information (Al-Omairi et al, 2020). Health information is more reliable as they are designed by experts (Chen et al, 2020) and e-government (Park and Lee, 2018).…”
Section: Source Credibility (Cre)mentioning
confidence: 99%
“…The human factor is still essential for decision-making (Athey, 2017). Also, we should prepare our public managers with the ability to learn and be aware of emerging technology, such as IoT (Chohan et al, in press;Ma et al, 2020aMa et al, , 2020b, blockchain (Hasan et al, 2021;Alam et al, in Press) and the latest learning technology for implementing them into the public services, such as MOOC (Al-Omairi et al, 2021;Cheng, in press;J. Cheng et al, in press;W.…”
Section: Discussionmentioning
confidence: 99%
“…In short, the basis for measuring a dropout in an online course is different from that of a traditional course. Only those learners who fully participate in MOOCs and have the intention to complete the course (Deboer et al, 2014), especially those from the developing countries should count towards this statistic (Al-Omairi et al, 2021). The extant research has recognized the problem of a high dropout rate, albeit with no finality on the reasons behind the high dropout rate.…”
Section: Research Backgroundmentioning
confidence: 99%